Establishment of Novel Genotoxicity Assay System Using Murine Normal Epithelial Tissue-Derived Organoids - Komiya, Masami; Ishigamori, Rikako; Naruse, Mie; Ochiai, Masako; Miyoshi, Noriyuki; Imai, Toshio; Totsuka, Yukari (Frontiers in Genetics, 2021)
Short-/middle-term and simple prediction studies for carcinogenesis are needed for the safety assessment of chemical substances. To establish a novel genotoxicity assay with an in vivo mimicking system, we prepared murine colonic/pulmonary organoids from gpt delta mice according to the general procedure using collagenase/dispase and cultured them in a 3D environment. When the organoids were exposed to foodborne carcinogens—2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and acrylamide (AA)—in the presence of metabolic activation systems, mutation frequencies (MFs) occurring in the gpt gene dose-dependently increased. Moreover, the mutation spectrum analysis indicated predominant G:C to T:A transversion with PhIP, and A:T to C:G and A:T to T:A transversion with AA. These data correspond to those of a previous study describing in vivo mutagenicity in gpt delta mice. However, organoids derived from the liver, a non-target tissue of PhIP-carcinogenesis, also demonstrated genotoxicity with a potency comparable to colonic organoids. Organoids and PhIP were directly incubated in the presence of metabolic activation systems; therefore, there was a lack of organ specificity, as observed in vivo. Additionally, PhIP-DNA adduct levels were comparable in hepatic and colonic organoids after PhIP exposure. Taken together, the organoids prepared in the present study may be helpful to predict chemical carcinogenesis.